2005
DOI: 10.1007/s00775-005-0641-9
|View full text |Cite
|
Sign up to set email alerts
|

Oxoiron(IV) porphyrin π-cation radical complexes with a chameleon behavior in cytochrome P450 model reactions

Abstract: There is an intriguing, current controversy on the involvement of multiple oxidizing species in oxygen transfer reactions by cytochromes P450 and iron porphyrin complexes. The primary evidence for the "multiple oxidants" theory was that products and/or product distributions obtained in the catalytic oxygenations were different depending on reaction conditions such as catalysts, oxidants, and solvents. In the present work, we carried out detailed mechanistic studies on competitive olefin epoxidation, alkane hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
152
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 162 publications
(172 citation statements)
references
References 79 publications
18
152
1
1
Order By: Relevance
“…As such, in the gas-phase the [Fe IV (O)(TPFPP +• )] + complex will preferentially react via aromatic hydroxylation over aliphatic hydroxylation with substrates. Nam et al [22] Subsequent computational modelling showed that the axial ligand affects the electron affinity and O-H bond strength (bond dissociation energy, BDEOH) and hence affected the relative barriers of aliphatic versus aromatic hydroxylation. [14b,23] To gain further insight into the intricate details of the bifurcation processes, below we will show a molecular orbital and valence bond interpretation of the mechanisms, but first we will discuss the experimental reaction trends.…”
Section: Discussionmentioning
confidence: 99%
“…As such, in the gas-phase the [Fe IV (O)(TPFPP +• )] + complex will preferentially react via aromatic hydroxylation over aliphatic hydroxylation with substrates. Nam et al [22] Subsequent computational modelling showed that the axial ligand affects the electron affinity and O-H bond strength (bond dissociation energy, BDEOH) and hence affected the relative barriers of aliphatic versus aromatic hydroxylation. [14b,23] To gain further insight into the intricate details of the bifurcation processes, below we will show a molecular orbital and valence bond interpretation of the mechanisms, but first we will discuss the experimental reaction trends.…”
Section: Discussionmentioning
confidence: 99%
“…[48][49][50][51] The primary evidence for proposing the multiple-oxidants hypothesis was that products and/or product distributions derived from the catalytic oxidations by CYP 450 and iron porphyrin models were different depending on reaction conditions such as catalysts (e.g., CYP 450 and their mutants), oxidants (e.g., H 2 O 2 , peracids, and iodosylarenes), and axial ligands of iron porphyrin catalysts (e.g., ligating and nonligating anions). 44,49,51 However, as we have discussed in the previous section, iron(IV)-oxo porphyrin π-cation radicals can exhibit diverse reactivity patterns under different circumstances, leading us to postulate that the different products and/or product distributions observed in iron porphyrin-catalyzed oxygenation reactions do not arise from the involvement of multiple oxidizing species but from a single oxidant under different environmental circumstances. 44 More strong experimental evidence for excluding the possibility of a "second electrophilic oxidant" in oxygen atom transfer reactions was obtained from the reactivity studies of iron(III)-hydroperoxo species in nucleophilic and electrophilic reactions, by using in situ-generated mononuclear non-heme iron(III)-hydroperoxo complexes that have been well characterized with various spectroscopic techniques.…”
Section: Multiple-oxidants Hypothesismentioning
confidence: 97%
“…44,49,51 However, as we have discussed in the previous section, iron(IV)-oxo porphyrin π-cation radicals can exhibit diverse reactivity patterns under different circumstances, leading us to postulate that the different products and/or product distributions observed in iron porphyrin-catalyzed oxygenation reactions do not arise from the involvement of multiple oxidizing species but from a single oxidant under different environmental circumstances. 44 More strong experimental evidence for excluding the possibility of a "second electrophilic oxidant" in oxygen atom transfer reactions was obtained from the reactivity studies of iron(III)-hydroperoxo species in nucleophilic and electrophilic reactions, by using in situ-generated mononuclear non-heme iron(III)-hydroperoxo complexes that have been well characterized with various spectroscopic techniques. 52 In this study, non-heme iron(III)-hydroperoxo intermediates did not exhibit any reactivities in both nucleophilic (e.g., aldehyde deformylation) and electrophilic (e.g., oxidation of sulfide and olefin) reactions (Scheme 4), demonstrating that non-heme iron(III)-hydroperoxo species are sluggish oxidants and that the oxidizing power of the intermediates cannot compete with that of iron(IV)-oxo complexes.…”
Section: Multiple-oxidants Hypothesismentioning
confidence: 97%
“…Although there are several studies demonstrating that axial ligands affect the reactivities of iron(IV)-oxo centers in biomimetic Cpd I analogs (15,16), only one of these studies reported the effect of a range of ligands on reaction rates (15), but no clear correlation between reactivity and some property of the axial ligand was discerned. More recently, with the synthesis of the first nonheme iron(IV)-oxo complex, [Fe IV (O)(TMC) (NCCH 3 )] 2ϩ (where TMC is 1,4,8,11-tetramethyl-1,4,8,11-tetraazacyclotetradecane) (17), we found that the axial CH 3 CN ligand can be replaced with anions and that these anions affected the reactivity of the iron(IV)-oxo unit (18)(19)(20).…”
mentioning
confidence: 99%